EBU’L-BEREKAT EL-BAĞDADİ’NİN MANTIK İLMİNE BAKIŞI - Ahmet Kamil Cihan (İslami İlimler Dergisi)
This research is about Abul Barakat al Baghdadi’s opinions on Logic. The aim of, functiol of, subject of logic, and its place in the classification of sciences is mentioned in this article. According to him, logic is important not for possibilaty of knowledge but also reasoning knowledge. The main and direct subject of logic is “meanings.” Also, words and writings are relevant to logic, indirectly. Logic is independent science in the classification of science. İt is also science of other sciences. The important of Baghdadi for logic is a giver a signal abandoning ontological logic to pure logic.